Práticas educativas:o uso do estudo dirigido e do seminário e suas contribuições para a aprendizagem significativa em química no 3º ano do ensino médio - Silva, Edneide Maria Ferreira da (2014)
Education in Brazil, in general, is not consistent with the real needs of its students, once that they do not achieve success in the external evaluations applied to them. To improve the teaching of Chemistry in High School, it is necessary the use of different methodologies that emphasize the use of data from everyday reality, through the use of simple and accessible language, which will make it possible to arouse in the students a critical and investigative character, making them become agents of their own learning process. This study aimed to analyze the pedagogical use of the educational practices of Guided Study and of Seminars to the Chemistry Teaching, based on the concepts of meaningful learning. This was a field research, descriptive and bibliographical in nature, with case study, following a quali-quantitative approach, and performed with students from the 3rd year of High School in a state school located in Maracanaú, metropolitan region of Fortaleza. For the implementation of this research, students were divided into groups, one of which had Chemistry classes through traditional methods, while the other groups had the teaching strategies of Guided Study, followed by the Seminars. The Guided Study was especially prepared for the development of this research, focused on the issues: “Carbon”, “Organic Functions”, “Isomerism” and “Organic Reactions”. For the strategy of Seminars it was used the book Napoleon's Buttons: 17 Molecules That Changed The History, by Penny Le Couteur and Jay Burreson , translated by Maria Luiza X. A. Borges (2006). The results of the usage of these strategies were evaluated through the application of tests that aimed to identify the applicability, in everyday routine, of the chemical concepts acquired along the activities, and to observe the changes regarding student behavior, as well as their genuine interest for the proposed activities. Comparing the two pedagogical practices applied, there was an increased interest by students and effective participation in the implementation of the Guided Study, consequently resulting in higher learning. As for the use of seminars, it was proved that they promoted a link between Organic Chemistry and History of Science/Chemistry. Thus, awareness of the interdependence between subjects gave the students a more critical vision, amplifying their understanding of the meaning of science. It was concluded that it is possible to work in an interdisciplinary and contextualized way, and the History of Science/Chemistry is one of the tools that enable this pedagogical task.